APLIKASI DOMPET DIGITAL BERBASIS ANDROID PADA BUS TRANSMETRO KOTA PEKANBARU - Gusrio Tendra; Suwarti Suwarti (Universitas Nusa Cendana, 2020)
Transmetro is a mass public transportation provided by the Pekanbaru city government, under the supervision of the Pekanbaru City Transportation Service. The travel costs offered on public transportation are fairly cheap, and very affordable for the middle to lower class. Each transaction carried out still uses the currency of exchange in the form of fixed currency provided by passengers who wish to travel. Sometimes not all passengers have the exact amount specified in the travel costs. Money back which is sometimes not available requires passengers to give up an amount of money they have. Therefore, this study aims to build a digital wallet application based on an Android device to simplify the transactions to be carried out. Only by filling in a sufficient balance in the application and scanning the QRcode at the time of the transaction, the transaction has been recorded automatically on the Transmetro party database without the need to recap the data.